Determination of optimum maturity stage of banana - Amin, MN; Hossain, MN; Rahim, MA; Uddin, MB (Bangladesh Journal of Agricultural Research, 2015)
Time of harvest based on maturity indices is very important for fruit quality. Fruits harvested before optimum maturity may not ripe adequately and may not develop adequate flavor, while fruits harvested late (over-matured) have a shorter postharvest life and deteriorate rapidly. Climacteric fruits can be harvested after reaching full maturation, and before reaching the ripening stage. The tissue culture suckers of BARI Kola1 and Sabri Kola varieties were used for the study. The experiment was conducted at the Farm Machinery and Postharvest Process Engineering Division, Bangladesh Agricultural Research Institute, Gazipur in 2009-10. Optimum maturity stage of banana fruits reduced the postharvest losses and extended the storage life of fruits. BARI Kola 1 and Sabri Kola reached to flowering stages 10 and 15 months after planting, respectively. The optimum maturity stages of BARI Kola 1 and Sabri Kola were found to 120 and 100 days after emergence of flowering (DAEF) in summer and 130 and 110 DAEF in winter seasons, respectively. Higher pulp to peel ratio and yield of both the varieties was found in summer than those of winter season. The pre-harvest loss of banana fruits started at the point when it just exceeded the optimum maturity stage. Decreasing trend of shelf-life and firmness of fruits for both the varieties were observed with the advancement of maturity. On the other hand, dry matter content, angularity, pulp to peel ratio, and yield of banana fruits increased with the advancement of harvesting days. Degree days of these varieties were found to be 1750 and 1620, respectively. Bangladesh J. Agril. Res. 40(2): 189-204, June 2015